Daniel Alcides Carrion’s death: a critical review - Salinas-Flores, David (2009)
Daniel Alcides Carrion’s experiment was a landmark in the history of Peruvian medicine, with much controversy, but perhaps the main topic of discussion is the cause of Carrion’s death. An objective fact has passed unnoticed in the last hours of the experiment: the administration of intravenous injections of phenic acid. In 1884, this was a therapy proposed for anthrax treatment in Peru. The doctors’ medical decision during Carrion’s agony probably did not consider giving blood transfusions to Carrion in order to experiment with this new treatment. They probably thought to repeat with bartonellosis the success described with phenic acid injections in a patient with anthrax, unaware of the now proven toxicity of phenic acid. The event precipitating Carrion’s death was probably phenic acid intoxication in a patient with bartonellosis in the anemic phase.